Chronic alcohol use and accompanying noncommunicable diseases - Oluwasegun Ayenigbara, Israel (Array, 2020)
Introduction. Heavy and chronic alcohol use connotes frequent, continuous and persistent consumption of alcoholic drinks over an extended period of time. Importantly, heavy consumption of alcohol causes many health problems to the drinker and the society at large, as over 5.1% of the global burden of morbidity and injuries are attributable to alcohol usage alone. Aim. The purpose of this study is to identify some of the noncommunicable diseases that are associated with chronic alcohol consumption through a systematic and narrative review, with detailed descriptions of the occurrences. Methods. A systematic and narrative review of literature that evaluates noncommunicable diseases associated with chronic alcohol consumption was carried out using Google, Medline and databases of major international health organizations. Keywords used as search terms were alcoholism, chronic alcohol use and heavy alcohol use; these terms were matched with occurrences and risk of noncommunicable diseases. Studies included in this review are clinical trials, meta-analyses, randomized controlled trials, and systematic and review articles. Results. The findings revealed that chronic alcohol use is either a single or joint risk factor for Alzheimer’s disease and dementia, arthritis, brain malfunction, cancer (most commonly of the oropharynx, larynx, oesophagus, liver, colon, rectum or breast), chronic obstructive pulmonary disease (COPD), diabetes, epilepsy, heart diseases and cardiovascular diseases, immune system dysfunction, malnourishment and vitamin deficiencies, mood disorders, bipolar disorder and depression, osteoporosis and bone malformation, pancreatitis, and ulcers and gastrointestinal problems. Conclusion.